Mechanical properties and influencing factors of vertical-vibration compacted unbound graded aggregate materials. (May 2021) - Deng, Changqing; Jiang, Yingjun; Zhang, Yu; Yi, Yong; Tian, Tian; Yuan, Kejia; Fan, Jiangtao
Highlights: A vertical vibration compaction method (VVCM) for the UGAM was proposed. Performance of UGAM fabricated by VVCM, HHCM and QSCM was compared. Mechanical properties of the UGAM fabricated by VVCM were analyzed. Abstract: Currently, heavy hammer compaction method (HHCM) and quasi-static-compaction method (QSCM) are primarily used to produce the unbound graded aggregate materials (UGAM) samples and their mechanical properties are measured to guide the design and construction of the UGAM base. However, few studies have focused on the mechanical properties of the UGAM produced using vertical-vibration compaction method (VVCM). Thus, this paper studies mechanical properties of the UGAM fabricated by the VVCM. The reliability of VVCM was evaluated by comparing the physical and mechanical properties measured in the field and in a specimen fabricated by the HHCM or QSCM. After discussing the influence of compactness, moisture content, gradation and stress on the mechanical properties of UGAM fabricated by VVCM, a prediction model of dynamic resilient modulus was established. The California bearing ratio (CBR) of the VVCM-fabricated UGAM was more than 92% of the field-measured CBR. The VVCM also exhibited a lower aggregate crushing rate than the HHCM and QSCM. The CBR and unconfined compressive strength increased linearly and nonlinearly with compaction degree, respectively. Moreover, the shear strength was a linear function of confining pressure, but resilient modulus nonlinearly increased with deviator stress. Moisture content was reduced by air drying and this increased the mechanical properties. The influence of various factors on the dynamic resilient modulus of UGAM could be accurately predicted by the established model. The performance of UGAM was improved after GM gradation than after GF gradation. Thus, this alternative compaction method is vital for enhancing the popularisation and application of UGAM.